The Influence of Perceived Price, Location and Service Quality on Customer Satisfaction at Kasmaran Pandu Raya Coffee Bogor - Saputra, Ricky Christian; Vitaharsa, Leonardo Indra (Asian Journal of Management Analytics, 2023)
This study aims to examine the perceptions of price, location, and quality of service in Pandu Raya Bogor Kasmaran coffee. Researchers used quantitative research using surveys with purposive samples and a population of 100 respondents. The data used is collected directly from each respondent with qualifications for more than two arrivals. Perception of price, location, and service quality Together produce a significant influence on customer satisfaction at Kopi Kasmaran Pandu Raya Bogor.